Energy Transition Policy options for sustainable development in South Africa - Mathe, Clive (University of the Witwatersrand, Johannesburg, 2024)
The South African energy sector is at a critical point in the nation's macroeconomic journey, playing a significant role in base industrial activities and standing as Africa's highest producer and consumer of energy. However, it faces challenges such as a disproportionately high Greenhouse Gas emissions compared to similar economies. South Africa's commitment to decarbonize the sector and achieve net-zero emissions by 2050 presents both opportunities and risks, influenced by various factors with high inter-factor causality. To unlock actionable insights on the energy sector transition, this study aims to model the energy system comprehensively, considering its complexity and dynamism. Specifically, it seeks to assess the implications of South Africa's decarbonization commitment, explore the potential of renewable energy adoption, and identify strategic pathways and mechanisms to accelerate the transition towards net-zero emissions. A combination of two computer-simulation-based modeling and analysis approaches is adopted for the research work. Systems dynamics is employed for secondary quantitative data modeling, capturing relationships among energy sector factors. Fuzzy cognitive mapping, coupled with expert knowledge solicitation through semi- structured interviews, unveils important causality relationships among systemic parameters. The integration of these approaches forms a hybrid model, overcoming limitations and providing actionable insights crucial for sector transition policy considerations. Through quantitative modeling, it is projected that coal decommissioning and renewable energy expansion could decrease power-sector carbon emissions by over 90% from approximately 0.26 Gt of CO2 in 2019 to around 0.02 Gt of CO2 by 2050. However, meeting the investment requirements for the proposed transition pathway remains a significant challenge. Accelerating renewable energy development by 20% is suggested to mitigate risks and activate a greener economy, leading to socio- political and economic benefits. VII In conclusion, the imperative for decarbonization in South Africa's energy sector is underscored, aligning with global decarbonization targets and ensuring socioeconomic stability. Strategic interventions, particularly in accelerating renewable energy deployment, are essential to navigate the transition effectively and realize the full potential of a sustainable energy future.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Energy Transition; Policies options, South Africa; Sustainable development; Social EquityEconomic Efficiency; Systems Dynamics; Fuzzy Cognitive Mapping; UCTD; SDG-8: Decent work and economic growth